Building a Culture of Academic Integrity: Meeting Students Where They Are - Salmon, Holly; Moist, Shannon (Canadian Perspectives on Academic Integrity, 2023)
How can we meet students where they are to provide academic integrity instruction? By moving to the centre of campus and engaging students in walk-up learning opportunities outside the classroom. In this presentation, faculty members from the Library and Learning Centre will share their collaborative experiences in creating new academic integrity supports for students in an institution where Academic Integrity does not fall under the umbrella of an institution's Teaching & Learning Centre or a dedicated Academic Integrity Office. Participants will learn about a new collaborative initiative to engage students in learning about academic integrity that includes a series of interactive activities in a central space on campus. This collaborative tabling between the Library, Learning Centre, and Student Life allows students to explore ideas they have, ask questions, and engage in learning activities outside the “normal” learning environment of classroom, library and tutoring spaces and connect the students to the services offered for deeper learning through knowledge of the available resources. Time will be reserved for others to share similar programming and ideas.